Accreditation of forensic laboratories as a part of the "European Forensic Science 2020" concept in countries of the Visegrad Group. (December 2015) - Pádár, Zsolt; Nogel, Mónika; Kovács, Gábor
Abstract: Globalising, cross-border crime has led EU Member States to improve methods of fighting crime on an international level as well as to increase the mutual recognition of collecting and analysing evidence by one another. In the interest of the regulated and scheduled implementation of the harmonization process, the Council of the EU made a decision of The Vision for European Forensic Science 2020 including the creation of a European Forensic Science Area and the development of forensic science infrastructure in Europe [EFSA 2020] to ensure the equivalence of professional forensic examinations. The collection, processing, use and delivery of forensic data will be based on equivalent minimum forensic science standards, and forensic service providers will work on the basis of a common approach to implement these standards that foster closer cooperation between them and criminal justice systems. The accreditation of forensic laboratories is a corner stone of the above mentioned objectives[1–3] . Ensuring the integrity of DNA profiles the Council issued decision 2008/616/JHA the application of EN ISO/IEC 17025 standard regarding the operation of testing and calibration laboratories has been ordered[4] . According to Council Framework Decision 2009/905/JHA on the accreditation of judicial expert laboratories, the laboratories have to be accredited until 30th November 2015[5] . We investigated the regulations, decisions and rules national and international measures of the given area.